Preparation of Phosphorylated Auricularia cornea var. Li. Polysaccharide Liposome Gel and Analysis of Its In Vitro Antioxidant Activity - Wenguang Fan; Xintong Jiang; Qinyang Li; Jiansheng Wang; Minghui Lv; Junmei Liu (Foods, 2024)
In this study, Auricularia cornea var. Li. polysaccharides (ACP) were used as the research object to prepare liposome gel and determine its antioxidant activity in vitro. Phosphorylated Auricularia cornea var. Li. polysaccharides (P-ACP) were prepared via the phosphorylation of ACP by the phosphate method. Additionally, phosphorylated Auricularia cornea var. Li. polysaccharide liposomes (P-ACPL) were prepared using a reverse evaporation method. Finally, phosphorylated Auricularia cornea var. Li. polysaccharide liposome gel (P-ACPLG) was prepared by dispersing the P-ACPL in the gel matrix. The results show that the phosphorylation of the P-ACP was 15.51%, the containment rate of the P-ACPL was 84.50%, the average particle size was (192.2 ± 3.3) nm, and the particle size distribution map had a homogeneous peak, resulting in the particle dispersion being uniform and the polydispersion index (PDI) being 0.134 ± 0.021. The average Zeta potential was (−33.4 ± 0.57) mV. In addition, the in vitro antioxidant activity of the P-ACPL was slightly higher than that of the ACP and P-ACP. After the P-ACPL was emulsified into P-ACPLG, the DPPH, hydroxyl radical clearance, and reducing the ability of P-ACPL remained unchanged. In general, the P-ACPLG prepared in this study has good antioxidant activity in vitro and can retain the antioxidant activity of P-ACPL in vitro well.